2007
DOI: 10.1016/j.neuroscience.2007.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Morphine preferentially activates the periaqueductal gray–rostral ventromedial medullary pathway in the male rat: A potential mechanism for sex differences in antinociception

Abstract: The midbrain periaqueductal gray (PAG), and its descending projections to the rostral ventromedial medulla (RVM), provides an essential neural circuit for opioid-produced antinociception. Recent anatomical studies have reported that the projections from the PAG to the RVM are sexually dimorphic and that systemic administration of morphine significantly suppresses pain-induced activation of the PAG in male but not female rats. Given that morphine antinociception is produced in part by disinhibition of PAG outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 65 publications
6
60
0
1
Order By: Relevance
“…Furthermore, there is substantial evidence that the PAG and descendant projections comprise a neural circuit essentially mediated by endogenous and exogenous opioid analgesics (Loyd et al, 2007;Wang & Wessendorf, 2002), which significantly attenuated activity after the microinjection of opioid antagonists in this region (Bernal et al, 2007). Therefore, our results suggest that PC has a significant ability by reducing the production of pro-inflammatory cytokine TNF-a, the migration of leukocytes, and the release of NO.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, there is substantial evidence that the PAG and descendant projections comprise a neural circuit essentially mediated by endogenous and exogenous opioid analgesics (Loyd et al, 2007;Wang & Wessendorf, 2002), which significantly attenuated activity after the microinjection of opioid antagonists in this region (Bernal et al, 2007). Therefore, our results suggest that PC has a significant ability by reducing the production of pro-inflammatory cytokine TNF-a, the migration of leukocytes, and the release of NO.…”
Section: Discussionmentioning
confidence: 61%
“…The spinal cord endorphin/μ-opioid receptor analgesic system is more robust and 'higher gain' in male vs. female rodents, which, if also true for humans, could be one mechanism underlying the greater female prevalence and intensity of chronic pain syndromes [81]. Sex differences in the anatomy and physiology of endogenous descending pain modulatory pathways have been reported in the rat [129,130]. These pathways are also sexually dimorphic in terms of their activation by persistent pain as well as in their responsiveness to exogenous opioids.…”
Section: How Does Pain Chronicity Contribute To Sex Differences In Pamentioning
confidence: 99%
“…Descending projections from PAG reach the rostral ventromedial medulla (RVM) and the activation of PAG-RVM pathway leads to a decrease in the perception of pain [26][27][28]. Initial studies conducted by Palazzo and colleagues concerning the putative role of TRPV1 channels within PAG-RVM descending nociceptive pathway showed that microinjection of capsaicin, a TRPV1 agonist, into the dorsal portion of the PAG (dPAG) increased the latency of nociceptive response in rats subjected to the plantar test, an acute nociceptive test [1].…”
Section: Introductionmentioning
confidence: 99%